2019
DOI: 10.1002/adts.201900109
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Screening of Metal Organic Frameworks as Fillers in Mixed Matrix Membranes for Flue Gas Separation

Abstract: High‐throughput computational screening of metal organic frameworks (MOFs) is performed to evaluate their performances as fillers in mixed matrix membranes (MMMs). Grand canonical Monte Carlo and molecular dynamics simulations are performed to calculate CO2 and N2 permeabilities of 7822 synthesized MOFs. This data are then combined with the experimentally reported gas permeability data of 14 different polymers using a theoretical permeation model. As a result, CO2 permeabilities and CO2/N2 selectivities of 109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Many highthroughput computational screening studies used either of the databases to investigate the gas storage and/or gas separation potentials of MOF materials. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Simon et al 27 recently provided an excellent review on molecular simulations of MOFs and discussed some shortcomings of computation-ready MOF databases. For example, the method used for solvent removal from MOFs could be too aggressive so that (i) the structural integrity of some MOFs without solvents may become questionable or (ii) the MOF could relax into a different form after the solvent removal or (iii) performing automatic solventremoval on large numbers of MOFs can lead to chemically inaccurate structures by accidentally removing an essential part such as the ligand or CBIs of the framework.…”
Section: Introductionmentioning
confidence: 99%
“…Many highthroughput computational screening studies used either of the databases to investigate the gas storage and/or gas separation potentials of MOF materials. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Simon et al 27 recently provided an excellent review on molecular simulations of MOFs and discussed some shortcomings of computation-ready MOF databases. For example, the method used for solvent removal from MOFs could be too aggressive so that (i) the structural integrity of some MOFs without solvents may become questionable or (ii) the MOF could relax into a different form after the solvent removal or (iii) performing automatic solventremoval on large numbers of MOFs can lead to chemically inaccurate structures by accidentally removing an essential part such as the ligand or CBIs of the framework.…”
Section: Introductionmentioning
confidence: 99%
“…In high-throughput screening studies on MMMs, although polymer permeability data used in theoretical models is generally measured at single-component gas conditions, simulations of MOFs are performed at infinite dilution to reduce the computational cost. 98,146 We also showed that when molecular simulations of MOFs are performed at infinite dilution (considering only one gas molecule in the framework), the results underestimated O 2 /N 2 membrane selectivities of MMMs calculated at single-component gas conditions (1 bar, 298 K). This result can be explained by the existence of gas-gas interactions at 1 bar and showed that simulation conditions of MOFs affect the predicted performance of MMMs.…”
Section: Mof-based Mmmsmentioning
confidence: 81%
“…143,144 Another way is to compute gas permeability of a large number of MMMs considering many MOF/polymer combinations and then identify the best ones offering the desired MMM properties. 146 It is important to note that the properties of MOF and polymer have a synergetic effect on those of MMMs. In our previous studies, [142][143][144]146 we showed that when a MOF filler is incorporated into a low permeable polymer, it generally affects gas permeability without any change in membrane selectivity.…”
Section: Mof-based Mmmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[75] Parameters such as reaction temperature and time, ligands, metal ion, molar ratio of starting materials, overall concentration, pH, and solvent are considered and established in MOF synthesis by the HT method. [145][146][147][148][149] The conventional MOFs, such as classical Fe 3+ and Al 3+ based MOFs with amino group (NH2) compounds of MIL-53-NH2, MIL-88-NH2, and MIL-101-NH2 with ligands of H2BDC-NH2, and also MIL-101(Cr), MIL-118, -120, -121, CAU-4, HKUST-1, and Fe-BTT have been developed by the HT method and reported by Stock and Biswas. [73] Recently, a novel work using HT method for screening the macroscale heteroepitaxial alignment MOFs from thousands of structures was presented based on surface chemical compatibility, lattice matching with substrate and interfacial bonding, which could be completed in a few days on a desktop workstation.…”
Section: High Throughput (Ht) Screening Of Mofsmentioning
confidence: 99%